2016
DOI: 10.2340/16501977-2166
|View full text |Cite
|
Sign up to set email alerts
|

Secondary health conditions and quality of life in persons living with spinal cord injury for at least ten years

Abstract: Secondary health conditions are common among persons with long-term spinal cord injury and the following secondary health conditions were independently associated with lower quality of life: musculoskeletal pain, pressure ulcers, problematic spasticity, and constipation. Minimizing the impact of secondary health conditions should be a priority in the long-term care of persons with spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 38 publications
10
103
0
2
Order By: Relevance
“…Many of these physical and psychological secondary conditions and complications have been associated with low activity and participation levels, such as difficulties with leaving from home and involvement in active recreation, as well as with low QoL (24)(25)(26). Our findings echo the conclusions of other studies for the high need for systematic, comprehensive, life-long, multi-disciplinary follow-up for people with SCI as a way to prevent and manage these secondary conditions (24,25).…”
Section: Reported Unbearable Physical and Psychological Problemssupporting
confidence: 80%
See 1 more Smart Citation
“…Many of these physical and psychological secondary conditions and complications have been associated with low activity and participation levels, such as difficulties with leaving from home and involvement in active recreation, as well as with low QoL (24)(25)(26). Our findings echo the conclusions of other studies for the high need for systematic, comprehensive, life-long, multi-disciplinary follow-up for people with SCI as a way to prevent and manage these secondary conditions (24,25).…”
Section: Reported Unbearable Physical and Psychological Problemssupporting
confidence: 80%
“…Many of these physical and psychological secondary conditions and complications have been associated with low activity and participation levels, such as difficulties with leaving from home and involvement in active recreation, as well as with low QoL (24)(25)(26). Our findings echo the conclusions of other studies for the high need for systematic, comprehensive, life-long, multi-disciplinary follow-up for people with SCI as a way to prevent and manage these secondary conditions (24,25). In addition, our findings, and in particular the preference of many respondents for peer mentors as most suitable to manage some of their problems, highlight the need for including peer mentors as an integral component of the multi-disciplinary team in all stages of SCI management.…”
Section: Reported Unbearable Physical and Psychological Problemsmentioning
confidence: 99%
“…1 These common disabling conditions negatively affect mood, sleep, quality of life, and participation in activities and active recreation as well as employment. [2][3][4][5][6][7] Neuropathic pain is present in 50-60% and spasticity in about 70% of individuals living with a SCI. 5,[8][9][10][11] Neuropathic pain is a multidimensional constellation of phenomenologically different symptoms and is defined as 'pain caused by a lesion or disease of the somatosensory nervous system'.…”
Section: Introductionmentioning
confidence: 99%
“…18 (13) years)). Adriaansen et al 28 found lower quality of life in persons living with their SCI for more than 10 years (mean 22 years) to be associated with musculoskeletal pain, ulcers, spasticity and constipation. Siddall et al also found pain to impact on spiritual well-being in people with long-term SCI.…”
Section: Discussionmentioning
confidence: 99%